Experimental Investigation of the Municipal Solid Waste Characteristics for a Gasification Based Waste-to-Energy Power Plants - Fazli Iqbal Pasha; Damora Rhakasywi; Nicky Yongkimandalan; Regina N. Lumbantoruan; Z. H. Putty Fauthyda; F. Firmansyah; Anisa Rahmah Kusuma; Rizki Apriza (International Journal of Marine Engineering Innovation and Research, 2025)
This study experimentally characterizes Municipal Solid Waste (MSW) feedstock to assess its suitability for gasification-based Waste-to-Energy (WtE) systems. Ten samples from different urban collection sites underwent thorough analysis using standardized ultimate and proximate methods, alongside bomb calorimetry on a dry basis, which helped to ensure the results accuracy. A strong positive correlation was observed between carbon and hydrogen content and gross calorific value, while oxygen, nitrogen, sulphur, and ash content exhibited a negative correlation with calorific potential. Notably, plastics and complex waste yielded the highest gross calorific values, around 30,000 kJ/kg and 31,600 kJ/kg, respectively, while high-ash content fractions recorded the lowest values at about 6,600 kJ/kg. The presence of volatile matter and fixed carbon positively impacts energy release, whereas ash dilutes fuel quality and increases heat absorption during combustion. The study suggests that pretreatment strategies, such as moisture reduction, ash fraction removal, and selective sorting for hydrocarbon-rich materials, effectively enhance fuel quality for gasification and reduce nitrogen and sulphur emission risks. The data reveal significant variability among different waste fractions, indicating that effective feedstock management and reactor design must address compositional heterogeneity to ensure reliable gasification performance.